วาทกรรมเรื่องความอ้วนความผอมในรายการโทรทัศน์สำหรับสตรี - สุนัที เลาะวิธี (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This research has 2 objectivities which were 1) to explore and to compile meanings of discourses on fatness and thinness on women s television programs. And 2) to study processes of discourses construction. This research used qualitative research methodology to analyze contents of fatness - thinness discourses on 3 women’s television programs: ‘Puen Ying, Palang Ying’ (Women’s friend, Women s Power), a social service program, See San Wan Sabai (Colorful Day), an entertainment program and Morning Health Club 1 a health - related program, including in-depth interview of program’s producers. The Analytical framework was based on discourse-analysis and a concept about physical human s body. Results of the research consist of 1) Meanings of fatness and thinness on women s television programs were constructed by 3 discourses: Medical Discourse which defined meanings under medical standard called Body Mass Index. The meaning which were reflected from text showed that fatness was the origin of illness and harmful for health. Second discourse was the Fashionable Discourse which found that the defining of meanings was influenced by standard of wearing and small size clothes. Therefore, fat women or anyone who could not wear in-trend clothes would become fashionable queerness. The last discourse was the discourse of beauty which constructed meanings by referring with slim size models and actresses. So the research found that thinness could lead to good opportunity in life and characteristics of meanings which were found in each issues were varied by mainstream discourse which defined thinness. Furthermore, the construction of identity between fat women and thin counterpart is the result of 3 mentioned discourse and also effected on relationship between discourse constructor and referred person. 2) Process of the construction of discourses on fatness and thinness showed up relationship between Discourse Practice and Sociocultural Practices which consist of 1) Text presenter was the doctor, mass media s worker and TV. announcer 2) The selection of issues depended on social current trend, TV program sponsor and interest of the producers. 3) Communicative strategy was presented by creating choices for audience both danger warning and diet suggestion. 4) Target group which was referred as discourse receivers and identified as fat - problem group who need suggestion on diet composed of single, marriage women and one who need to work in an entertainment industry. Furthermore, research also found that under process of constructing discourse, there has been the characteristic that coincided with social mainstream discourse namely medical, fashionable and sexuality discourse which support thinking and ideology of thinness. Under process of production, the research also found that TV. producers had idea to produce text depending on attribute of TV. Programs